Konstruksi Relasi Dialog Ilmu Sosial dan Agama melalui Pendekatan Epistemologi Titus - Illahiyah, Susan Diqrul; Nafis, Muhammad Muntahibun; Ahsan, Muhammad Fikri (Media: Jurnal Filsafat dan Teologi, 2024)
The positivistic style in the development of science in the modern period resulted in the dichotomy of science and religion and the loss of moral values, giving rise to many wars. In this case, religion is considered a moral control that maintains social harmony. This research aims to discover the relationship between social science (as a form of scientific knowledge) and religious science, as well as efforts to shape the relationship between the two. This research is a library research study using the Titus epistemological approach. This research found that firstly, the objects of study in social science and religious science are compatible with humans and their environment, even though in religion the object of study is physical and metaphysical, while in social science the object is based on reason and empirical. Second, the research methodology of social science is different from religious science except in the case of hermeneutics. Third, the concept of validity between the two is different. From these three findings, it can be concluded that the ‘dialogue’ relations between social science and religious science in terms of epistemology is in humans and their environment, and the existence of hermeneutics in its methodology.